Perfil fermentativo e valor nutricional de silagens de milho (zea mays l.) e aveia branca (avena sativa l.) colhidas com baixo teor de matéria seca e inoculadas com diferentes doses de aditivo microbiano e enzimático - Destri, Jaqueline (2021)
One of the most important aspects of the ensiling process consists of harvesting with an adequate dry matter content between 30 and 40%; however, due to countless factors, these values are not always reached. Thus, the objective was to evaluate whether the fermentative profile and the nutritional value of corn and oat silages harvested with low dry matter content were influenced by different doses of enzymatic microbial additive. The experiment was carried out in an experimental area belonging to the Dairy Cattle Teaching and Research Unit of the Universidade Tecnológica Federal do Paraná, Dois Vizinhos Campus. The corn was sown on November 7, 2018, and the harvests were carried out on February 5 and 12, 2019. The oat crop was established on April 18, 2019, and the harvests were carried out on July 16 and August 1, 2019. The inoculant was added to the crushed mass during the compaction at doses of 0; 500; 1,000; 1,500; and 2,000 mg/kg-1 of fresh material. The fermentative profile was estimated by analyses for dry matter recovery, gas losses, losses from effluents, pH, buffering capacity, ammoniacal nitrogen, soluble sugars, and short-chain volatile fatty acids (lactate, acetate, propionate, butyrate). The nutritional value was determined through chemical analyses for ash, crude protein, starch, neutral detergent fiber, acid detergent fiber, lignin, hemicellulose, cellulose, and in vitro ruminal degradation. The corn silage harvested with a higher dry matter content showed better results than the silage with a lower dry matter content. The lowest dry matter content resulted in the best fermentation profile, nutritional value, and in vitro ruminal degradation for the oat. The enzymatic microbial additive showed a positive effect on both ensiled crops.